Blockchain and Cryptocurrencies Technology: a survey - Bashar Ibrahim Hameed (Society of Visual Informatics, 2019)
Blockchain Â and Cryptocurrency has gotten wider considerations as of late. The decentralized digital Cryptocurrency Â and its underlying â€œBlockchain â€ technology has created much excitement in the technology community. The financial technology sector sees high potential value in Cryptocurrency Blockchain Â protocols, or distributed-ledger technology. The key advantage of this technology lies in the fact that it enables the establishment of secured, trusted, and decentralized autonomous ecosystems for various scenarios, especially for better usage of the legacy devices, infrastructure, and resources. In this paper, we presented a systematic investigation of Blockchain Â and Cryptocurrencies with explained simply in a way that Cryptocurrency is a form of digital currency that is being used to make transactions using a ledger known as Blockchain Â which is a decentralized system of banking in which there is no centralized authority and all the control lies on an algorithm and its controlling users. Blockchain , a financial tool that can potentially play an important role in the sustainable development of the global economy. The new technology is expected to bring massive benefits to consumers, to current banking system and to the whole society in general.Â